2022
DOI: 10.20473/ijosh.v11i2.2022.187-194
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Working Period and Exercise Routines with Musculoskeletal Complaints on Batik Craftsmen

Abstract: Introduction: Asosiasi untuk Demokrasi dan Kesejahteraan Sosial (Ademos) was founded as a form of anxiety towards rural communities whose majority of the population does not receive enough attention and access to economic development. One of the empowerment programs is a program to improve the quality of the Bojonegoro batik craftsmen. Workers can work more than 8 hours a day in a sitting and bending position for long periods of time. This study aimed to determine the correlation between the length of work and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…This triggers biological changes in muscle strength and endurance, which result in an increased risk of musculoskeletal disorders. 12 The results of this study showed that the majority of participants only experienced a low risk of musculoskeletal disorder. The age factor can affect the results because the participants in this study were 18-23 years old.…”
Section: Discussionmentioning
confidence: 66%
“…This triggers biological changes in muscle strength and endurance, which result in an increased risk of musculoskeletal disorders. 12 The results of this study showed that the majority of participants only experienced a low risk of musculoskeletal disorder. The age factor can affect the results because the participants in this study were 18-23 years old.…”
Section: Discussionmentioning
confidence: 66%
“…If the muscle receives repeated loads for an extended period, it can cause complaints in the form of damage to joints, ligaments and tendons (Schlussel and Maykel, 2019). Complaints of MSDs can occur when the muscle receives a load with a static posture, or the work is done repetitively, and the work is done over a long period (Dong et al, 2022;Pramesti and Arini, 2022). The workload given to workers must correspond to their physical and psychic abilities of the workers concerned.…”
Section: Resultsmentioning
confidence: 99%
“…This can be exacerbated by ergonomic hazards in the workplace, for example, jobs that require repetitive movements and take place every day, and workers use much energy to complete the job. If the activity lasts a long time and continuously, the a higher risk of musculoskeletal complaints such as CTDs [18]…”
Section: Years Of Service As a Risk Factor For Complaints Of Ctdsmentioning
confidence: 99%